Extensión of the arbitration agreement to a third party and international public policy: commentary on the order of the Tribunal Superior de Justicia (High Court of Justice) of the Basque Country (Civil and Criminal Chamber) No. 277/2018, of November 7th, 2018 - Casado Abarquero, Marta (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
In this ruling, the High Court of Justice of the Basque Country analyzes the conditions that must be met so that the extension of the effects of an arbitration agreement to a non-signatory third party is respectful of the public order of the forum. It also analyzes some previous procedural aspects, such as the viability of an application for the non-recognition of the foreign award, or of the request of recognition of a partial award.